Analisis Teori Keadilan Jhon Ralws terhadap Pembatasa Hak Pilih TNI dalam Bingkai Demokrasi Pancasila - Candra Vira Faradillah (Legislatif, 2023)
This research discusses the restriction of TNI's voting rights in the context of Pancasila democracy, focusing on the dualism between the fulfillment of human rights and justice. A critical analysis of John Rawls' theory of justice is used as a conceptual framework to investigate the impact of such restrictions on democratic principles oriented towards the fulfillment of human rights and social justice. The results of this research are expected to provide valuable insights into the conceptual dilemma arising from this dualism, as well as provide a basis for constructive debate on whether or not such restrictions should be imposed. This research is normative-empirical legal research with data collection techniques in the form of an interview with a respondent to find out his experience related to the topic of study. The results of this study show that the limitation of TNI's voting rights cannot be separated from the history of TNI's involvement in government politics which is considered too overpowering and endangers the interests and creates injustice for the Indonesian people at large. The unequal position between the two is also feared to create unfair elections. Thus, when viewed from John Rawls' theory of justice, the restriction of TNI's voting rights is not a form of state discrimination against TNI members, but rather a form of affirmative action to create fair elections within the framework of Pancasila democracy.